Toxoplasma membrane inositol phospholipid binding protein TgREMIND is essential for secretory organelle function and host infection - Houngue, Rodrigue; Sangaré, Lamba Omar; Alayi, Tchilabalo Dilezitoko; Dieng, Aissatou; Bitard-Feildel, Tristan; Boulogne, Claire; Slomianny, Christian; Atindehou, Cynthia Menonve; Fanou, Lucie Ayi; Hathout, Yetrib; Callebaut, Isabelle; Tomavo, Stanislas (Cell reports (Cambridge), 2024)
Apicomplexan parasites possess specialized secretory organelles called rhoptries, micronemes, and dense granules that play a vital role in host infection. In this study, we demonstrate that TgREMIND, a protein found in Toxoplasma gondii, is necessary for the biogenesis of rhoptries and dense granules. TgREMIND contains a Fes-CIP4 homology-Bin/Amphiphysin/Rvs (F-BAR) domain, which binds to membrane phospholipids, as well as a novel uncharacterized domain that we have named REMIND (regulator of membrane-interacting domain). Both the F-BAR domain and the REMIND are crucial for TgREMIND functions. When TgREMIND is depleted, there is a significant decrease in the abundance of dense granules and abnormal transparency of rhoptries, leading to a reduction in protein secretion from these organelles. The absence of TgREMIND inhibits host invasion and parasite dissemination, demonstrating that TgREMIND is essential for the proper function of critical secretory organelles required for successful infection by Toxoplasma. [Display omitted] •TgREMIND is a membrane-associated protein binding to PIP2 lipids•Both F-BAR domain and REMIND of TgREMIND are required for PIP2 binding•TgREMIND is essential for the biogenesis of rhoptries and dense granules in Toxoplasma•Inactivation of TgREMIND abolished Toxoplasma host cell invasion and dissemination In this study, Houngue et al. describe an essential role for the uncharacterized protein named TgREMIND, for regulator of membrane-interacting domain, in the biogenesis of rhoptries and dense granules, two secretory organelles that contain virulence factors released during and after Toxoplasma cell invasion.